Explaining the Limitations of Agricultural Intensification Initiatives in Sulawesi, Indonesia - Kelley, Lisa C. (Frontiers in Sustainable Food Systems, 2020)
This paper examines why cacao intensification initiatives have failed to significantly increase smallholder yields, improve livelihoods, or slow the pace of land use and cover change in Southeast Sulawesi, Indonesia. I first draw on land use surveys, household surveys, and remotely sensed data (1972-2015) to show how most households across four study villages are transitioning away from cacao amid sustained declines in yields and accelerating forest cover loss for non-cacao commodities. I then combine secondary data and in-depth interviews to show how cacao intensification initiatives have remained disconnected from the power and resource access relations necessitating smallholder livelihood movement away from cacao. Such relations include the dynamics of supply chain concentration, land control, and inequitable access to land and land-based livelihood opportunity that are deteriorating the economics of cacao production and informing smallholders' growing reliance on off-farm, extra-local work. Findings presented here illustrate the tensions between these ongoing livelihood shifts and the full-time farming focus required to successfully enhance yields. They also reiterate the limitations of any approach to agricultural sustainability that remains narrowly production or commodity-centric.